Diagnóstico sectorial de las organizaciones de la división transporte del cantón Loja - Maza Correa, Gabriela Michelle (2024)
The sectoral Diagnosis of the organizations of the transportation division of Loja was an exhaustive study that sought to analyze and evaluate the current situation of the companies and entities related to transport in a local way. The present work has as main objective elaborate an analysis of the sector, of the organizations of the land transportation division of the Loja canton, in order to provide averages for the companies that can have a solid basis for decision making. The methodology was the mixed, descriptive exploratory type, as the methods used, inductive, deductive, synthetic, analytical, cross-sectional design and the research techniques were surveys, which were applied to the twelve cooperatives and interparish, intercantonal, interprovincial and international companies of the Loja canton. The results generated from the fulfillment of the specific objectives, allowed the identification of various performance indicators, in which the average of different areas of the organizations were evaluated, such as internal processes, and customer service, in the same way, the financial indicators were measured aspects such as profitability, liquidity, indebtedness, ROA of large companies with an average of 0.21%, medium 1%, and small 2% therefore, the average ROE of large companies is 1%, medium 1%, small 4%. The diagnosis of the transportation sector is valuable for converting data into useful information. This has made it possible the evaluation of sector performance and the adoption of informed decisions,strategies that contribute to the development of the Loja canton and the well being of its inhabitants.